Percepções e práticas em relação ao patrimônio "Serra do Cajueiro", Itabaiana, Sergipe - Loureiro, Marister Alves (2013)
Social and environmental problems have never been so evident as today. Ways of using, and even appropriation of resources and/or natural assets have been questioned and analyzed nowadays. The creation of protected natural areas has become a precautionary measure and also normative in order to provide future generations the right to use these resources / assets. Thus, this analysis aims to ponder over the perceptions and practices of residents, visitors and managers in respect to Cajueiro Mountain Range, Itabaiana, Sergipe. This research is embedded in the whole of the National Park of Sierra Itabaiana. The descriptive exploratory research investigates the perceptions and practices of individuals related to the Serra do Cajueiro, rise the elements of perceived Serra, identify conservation practices in relation to it and assess whether Cajueiro is considered an asset for those who use it. The interdisciplinary nature of this research is done through the joints involving the fields that pass by the various disciplines related to the social, environmental, cultural, spatial and political. For data collection in the field research, it was used the techniques of passive observation and semi-structured interviews. The instruments used were mental maps and interviews in the formal and informal ambit. Information was worked using the content analysis and the mental maps were tabulated and analyzed taking into consideration the natural elements, constructed and human. The results showed that perceptions of residents and visitors do not converge with the practices, but for the residents, these routine practices establish a functional linkl and/or symbolic, configurating the Serra do Cajueiro as foundational to build the life history of those who use it in their daily lives. For visitors Serra is considered an asset from the perspective of the process of bureaucratization in which it is inserted.